PENCITRAAN PEREMPUAN BUTON DALAM NOVEL DI BAWAH BAYANG-BAYANG ODE KARYA SUMIMAN UDU: STILISTIKA - Rahmah Al Haqq, Nur (JURNAL ILMU BUDAYA, 2017)
This study aims to explain (1) Form style-based diction in the novel Di Bawah Bayang-Bayang Ode by Sumimn Udu. (2) Buton female imagery is strung as diction in the novel Di Bawah Bayang-Bayang Ode by Sumiman Udu. The results showed that the style of language that forms the female imagery consists of based on the language style of diction constituents formed by nouns, verbs, and adjectives. The female imagery that describes women Buton is seen from the three dominant characters mentioned. The results showed that the style of language that forms the female imagery consists of a figurative language style that is a (1) metaphor, (2) simile, (3) personification, and a rhetorical language style that is hyperbole. Based on the language style of diction constituents are formed by (1) nouns, (2) verbs, and (3) adjectives.